(untitled) (ModaPalavra e-periódico, 2023)
This paper analyzes the visual construction of the Vendedora de Cheiro (1947), based on the work of the artist Antonieta Feio, highlighting her dress and adornment styles, seeking to discuss how imagery and historical references built on such construction. The social significance such modes today, shall also be discussed as it is still alive in the popular imagination, so much so that this figure is seen as an indicator of a specific visuality of the Paraense Woman, thus configuring a local identity.